(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2014)
After assuming the fact of the recurrence of economic cycles and crises, and after identify some of the causes for the one we are living in nowadays, the article critically reflects on the concept of CSR from a theoretical point of view. In orderto connect some recent institutional providence with a robust idea for CSR, it will be bet for a moral approach, where CSR–beyond the legal requirements; but far from any kind of arbitrary practices– is understood from the strategy andin line with the telos, i.e., the very raison d’être for companies and businesses insociety, in search for the Common Good.